Girls and the school ball: A matter(ing) of space and time. (November 2019) - Ingram, Toni
Abstract: This article employs feminist new materialist thought to explore the spatial-material practice of the school ball (prom). Drawing on Barad's (2007) concept of spacetimemattering, it offers a rethinking of the schooling practice in relation to space and time. Rather than an isolated spatial-temporal event, the school ball is conceptualised as a continual process of becoming through shifting entanglements of space, time and matter. The aim of the article is to consider how the school ball is intra-actively produced through multiple spaces and temporalities, troubling popular constructions of the ball as a milestone in a 'coming of age' trajectory. Establishing the entanglement of space, time and matter opens up possibilities for imagining the school ball-girl in ways that do not rely on linear and developmental logic. Through the continual (re)configuring of spacetimematter, the ball-girl is not situated in a particular moment in time but entangled with space, time and matter. Highlights: The school ball is a continual process of becoming that occurs across multiple spaces and temporalities. Bodies, space and time are materialised through the dynamics of intra-activity. Spatiality and temporality are co-existing forces in the becoming of the school ball-girl. Ball-girl becomings are constantly reconfigured through multiple and non-linear spacetimematterings.